1975
DOI: 10.1126/science.1094539
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Cycle Oscillation: Reciprocal Discharge by Two Brainstem Neuronal Groups

Abstract: During the sleep cycle in cats, neurons localized to the posterolateral pole of the nucleus locus coeruleus and the nucleus subcoeruleus undergo discharge rate changes that are the opposite of those of the pontine reticular giant cells. The inverse rate ratios and activity curves of these two interconnected populations are compatible with reciprocal interaction as a physiological basis of sleep cycle oscillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
486
1
13

Year Published

1976
1976
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,119 publications
(528 citation statements)
references
References 12 publications
20
486
1
13
Order By: Relevance
“…Complex attractors represent imperfect oscillators within bounded orbits, modeling periodic functions common in nature. Oscillatory cycling (Hobson et al, 1975) and chaotic attractors (McCarley and Massaquoi, 1986) modeled REM on the basis of REM-on and REM-off neuronal activities. The argument regarding the existence of ultradian oscillators is far from closed, as it is becoming increasingly difficult to refute the likelihood of a genetic regulation of sleep physiology and its ultradian markers.…”
Section: Discussionmentioning
confidence: 99%
“…Complex attractors represent imperfect oscillators within bounded orbits, modeling periodic functions common in nature. Oscillatory cycling (Hobson et al, 1975) and chaotic attractors (McCarley and Massaquoi, 1986) modeled REM on the basis of REM-on and REM-off neuronal activities. The argument regarding the existence of ultradian oscillators is far from closed, as it is becoming increasingly difficult to refute the likelihood of a genetic regulation of sleep physiology and its ultradian markers.…”
Section: Discussionmentioning
confidence: 99%
“…23) The discharge activity of these neurons is highest during waking, decreases during slow-wave sleep, and is virtually absent during REM sleep. [4][5][6] In the absence of REM sleep, these neurons fire continuously, resulting in reduced receptor sensitivity 24,25) and changes associated with NA synthesis and metabolism. 26,27) Actually, the turnover and metabolism of NA are elevated both during and after REMSD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there may be a positive association between this animal model and a hyperfunctional status of noradrenergic systems since the firing of noradrenergic neurons in locus ceruleus (LC) continuous during rapid eye movement (REM) sleep deprivation. [4][5][6] ADHD is a childhood psychiatric disorder characterized by the presence of symptoms in three domains: inattention, impulsivity, and motor overactivity. 7) It has been suggested that these symptoms may be due to a combination of alerting deficits and executive-control deficits involving the prefrontal cortex.…”
mentioning
confidence: 99%
“…In doing so I will test the current understanding of the role the SubC plays in maintaining motor atonia. Furthermore, I will provide the quantitative muscle tone analysis lacking in existing SubC studies [12]. A knockout mouse which does not express the hypocretin ligand was developed, and it displayed sleep dysregulation which is similar to both human and canine narcolepsy.…”
Section: Section 2 -Aimsmentioning
confidence: 99%